Selected Euro-Area Countries : The Determinants of Growth; The Experience in the Southern European Economies of Greece and Portugal. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2002)
This paper reviews the recent growth experience of the Greek and Portuguese economies and their determinants, comparing it with the rest of the euro area as well as a large set of other economies. Estimates from fixed effects panel and cross-section regressions are used to estimate how changes in economic policies and structural reforms have been translated into growth during 1980-99. These estimates help to explain the slow growth performance of the Greek economy from 1980 up to the mid-1990s, and the acceleration of growth in recent years.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet